Identification of the porcine IG-DMR and abnormal imprinting of DLK1-DIO3 in cloned pigs - Li, Junliang; Yu, Dawei; Wang, Jing; Li, Chongyang; Wang, Qingwei; Wang, Jing; Du, Weihua; Zhao, Shanjiang; Pang, Yunwei; Hao, Haisheng; Zhao, Xueming; Zhu, Huabin; et al. (Frontiers in Cell and Developmental Biology, 2022)
Correct reprogramming of the DLK1-DIO3 imprinted region is critical for the development of cloned animals. However, in pigs, the imprinting and regulation of the DLK1-DIO3 region has not been systematically analyzed. The objective of this study was to investigate the imprinting status and methylation regulation of the DLK1-DIO3 region in wild-type and cloned neonatal pigs. We mapped the imprinting control region, IG-DMR, by homologous alignment and validated it in sperm, oocytes, fibroblasts, and parthenogenetic embryos. Subsequently, single nucleotide polymorphism-based sequencing and bisulfite sequencing polymerase chain reaction were conducted to analyze imprinting and methylation in different types of fibroblasts, as well as wild-type and cloned neonatal pigs. The results showed that Somatic cell nuclear transfer (SCNT) resulted in hypermethylation of the IG-DMR and aberrant gene expression in the DLK1-DIO3 region. Similar to wild-type pigs, imprinted expression and methylation were observed in the surviving cloned pigs, whereas in dead cloned pigs, the IG-DMR was hypermethylated and the expression of GTL2 was nearly undetectable. Our study reveals that abnormal imprinting of the DLK1-DIO3 region occurs in cloned pigs, which provides a theoretical basis for improving the cloning efficiency by gene editing to correct abnormal imprinting.